2019
DOI: 10.7759/cureus.4824
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Lumbar Interdural Cyst with Intradural Expansion and Compression of the Cauda Equina: Case Report and Surgical Video

Abstract: Intradural arachnoid cysts are common entities that can be congenital, or caused by infectious, inflammatory, or even traumatic processes. However, true "inter"-dural cysts formed between the two lamellae of the lumbar dura without any fistulous arachnoid connection are rare. We present the case of a post-traumatic interdural cyst formation of the lumbar spine that compressed the roots of the cauda equina causing acute unrelenting pain. The cyst walls were formed by the true dural layers, and the cavity was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although seven cases of interdural spinal cysts have been reported previously, some of these novel cases have only recently been described (Table 1). [2][3][4][5][6] Herein, we also report this novel type of spinal cyst, which was not previously classified. Even though Sajjad et al 6 already suggested a revised classification that included SMCs, we further propose a modified classification that includes interdural cysts with and without communication with the arachnoid space via the fistula.…”
Section: Discussionmentioning
confidence: 83%
“…Although seven cases of interdural spinal cysts have been reported previously, some of these novel cases have only recently been described (Table 1). [2][3][4][5][6] Herein, we also report this novel type of spinal cyst, which was not previously classified. Even though Sajjad et al 6 already suggested a revised classification that included SMCs, we further propose a modified classification that includes interdural cysts with and without communication with the arachnoid space via the fistula.…”
Section: Discussionmentioning
confidence: 83%